EVALUASI TOKSISITAS INSEKTISIDA TERHADAP IKAN NILA (Oreochromis niloticus) - Forita Dyah Arianti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2004)
Evaluation of acute toxicity of endosulfan insecticide in natural water environment was conducted to know its potential negative effect to the Nile (Oreochromis nitoticusi. Using static toxicity test method, the acute toxicity of7 endosulfan concentration levels were tested afterstandardized for 96 hours in the solution of water from river, pond and paddy field. Four replications were implemented into those treatment and ground water was being a control. The size of Nile used in the examination was 3-5 gr/tails in weight. Result of the examination was revealed by medium lethal concentration value LC50 -96 hours. The result indicated that insecticide of endosulfan in the solution of water from three kind environment had the high toxicity effection the Nile. The values of LC50 -96 hours were 6.00 mg/Lin the river water, 4.61 mg/Lin the pond water and4.51 mg/Lin the paddy field water, respectively. The difference of those values was caused by the difference of water quality such as total hardess, organic matters, total and suspended solid, and endosulfan residue in the water.